5x+60=5x

Simple and best practice solution for 5x+60=5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+60=5x equation:


Simplifying
5x + 60 = 5x

Reorder the terms:
60 + 5x = 5x

Add '-5x' to each side of the equation.
60 + 5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
60 + 0 = 5x + -5x
60 = 5x + -5x

Combine like terms: 5x + -5x = 0
60 = 0

Solving
60 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 449/0.42= | | 16/5-20x=8 | | 2500+100x+x^2= | | log(5x+1)=1.2 | | y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 | | y+2.4=7.33 | | 8+3n-5=9n+9-5 | | 2[2(3x-1)+3]-2(2x+5)=2(3x-3) | | 4+t^3=-3 | | s*6-43=83 | | 1+25=2x+20 | | 2[2(8x-1)+3]-2(2x+5)=2(3x-3) | | 2[2(83x-1)+3]-2(2x+5)=2(3x-3) | | 5x-1=19x | | 4a+19b-12a-10b= | | y=25+.57x | | 22x=16 | | 4(2a-1)-7a=4 |

Equations solver categories